Black women's same-gender dating preferences - Maldonado, Jessany (Journal of Black Sexuality and Relationships, 2024)
Scholarship exploring Black women-loving women's (Black WLW) romantic attraction to one another is scarce. Using a mixed methods design, this qualitative analysis reveals that Black WLW wield unwavering expectations as it pertains to dating qualifications. Characteristically, Black WLW prefer potential mates to have ethnic pride, intelligence, confidence, communication skills, and career ambition. Physically, Black WLW prefer potential mates who are curvaceous, and brown and/or dark-skinned in skin tone—especially if they themselves share the same features. Congruent with previous scholarship, Black WLW assign more value to an individual's character, aura, and personality over physical attributes when assessing attractiveness and desirability.
Keywords: dept.wgs; peer-reviewed